The Chemistry Interest Divide: Male Vs. Female Students at Penajam Paser Utara High School - Aprilia Sandra Kartika; Mukhamad Nurhadi; Maasje Catherine Watulingas (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Maritim Raja Ali Haji, 2026)
Learning interest is one of the factors that greatly influences students’ success in understanding the subject matter. In high school chemistry learning, learning interest plays an important role because chemistry requires conceptual understanding, analysis, and application in everyday life. However, in reality, students’ learning interest often differs between male and female students. Gender is assumed to be one of the factors influencing these differences, whether in terms of participation, or tendencies in the learning process. This study aims to determine the level of learning interest of male and female students in chemistry subjects. This research employed a quantitative descriptive design with the population consisting of senior high school students in the PPU region, using the proportionate stratified random sampling technique. The sample was determined using the Slovin formula with a margin of error of 10%, resulting in a total of 113 students, consisting of 47 male students and 66 female students. Data were collected using a non-test technique in the form of a learning interest questionnaire. The final results showed that the percentage of learning interest among male students was 72%, indicating that most male students had a high level of learning interest in chemistry. Meanwhile, female students achieved a percentage of 82%, which indicates that almost all female students had a very high level of learning interest in chemistry.